2012
DOI: 10.1158/0008-5472.can-11-0735
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cadmium Exposure and Risk of Postmenopausal Breast Cancer: A Population-Based Prospective Cohort Study

Abstract: The ubiquitous food contaminant cadmium has features of an estrogen mimetic that may promote the development of estrogen-dependent malignancies, such as breast cancer. However, no prospective studies of cadmium exposure and breast cancer risk have been reported. We examined the association between dietary cadmium exposure (at baseline, 1987)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 49 publications
4
108
5
1
Order By: Relevance
“…Comparing the highest quartile with the lowest, the OR for breast cancer among Long Island women was 2.69 (95% 1.07-6.78) while the OR among women in the NHANES was 2.50 (95% 1.11-5.63). In support of a causal role for cadmium exposure in breast cancer, Julin et al (2012a) reported that dietary cadmium intake was positively associated with overall breast cancer in the 12.2-yr cohort of 55,987 postmenopausal Swedish women. Comparing the highest tertile with the lowest tertile of dietary cadmium intake, rate ratio (RR) for all-type breast cancer was 1.27 (95% CI, 1.07-1.50) and RR for ER (+) tumors was 1.25 (95% CI, 1.03-1.52).…”
Section: Metallothionein Sequestration and Cadmium's Long Half-lifementioning
confidence: 98%
See 1 more Smart Citation
“…Comparing the highest quartile with the lowest, the OR for breast cancer among Long Island women was 2.69 (95% 1.07-6.78) while the OR among women in the NHANES was 2.50 (95% 1.11-5.63). In support of a causal role for cadmium exposure in breast cancer, Julin et al (2012a) reported that dietary cadmium intake was positively associated with overall breast cancer in the 12.2-yr cohort of 55,987 postmenopausal Swedish women. Comparing the highest tertile with the lowest tertile of dietary cadmium intake, rate ratio (RR) for all-type breast cancer was 1.27 (95% CI, 1.07-1.50) and RR for ER (+) tumors was 1.25 (95% CI, 1.03-1.52).…”
Section: Metallothionein Sequestration and Cadmium's Long Half-lifementioning
confidence: 98%
“…Breast cancer, Sweden (Julin et al 2012a), prospective, 55,987 postmenopausal women, 12.2-yrs observation.…”
Section: Metallothionein Sequestration and Cadmium's Long Half-lifementioning
confidence: 99%
“…One contaminant that has emerged in the literature as being associated with breast cancer risk is cadmium [53][54][55][56][57][58][59], with one study finding a two-fold increase in risk among women in the highest versus lowest quartile of urine cadmium level [56]. Another study found a positive association between dietary cadmium intake and risk of breast cancer in postmenopausal women [55].…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…Other potential mechanisms include inhibition of apoptosis or DNA repair, increased oxidative stress, or action as a metalloestrogen [55,57].…”
Section: Environmental Exposuresmentioning
confidence: 99%
See 1 more Smart Citation